Legal Measures Undertaken by Public Authorities in Poland for Prevention and Combating COVID-19 - Mełgieś, Katarzyna (Medicine, Law & Society, 2021)
The state is a special purpose organization and the directions of its activities are determined by public tasks. One of them is to ensure an efficient health care system, also effective in emergency situations such as those caused by an infectious disease pandemic COVID-19. In particular, legal instruments are used to create it, selected by the rulers within the limits set by law, including the applicable international standards, at the discretion of local governing authorities. The whole system is completed with organizational, medical and finally financial solutions. However, it is due to the fact that public authorities move around in the public space, due to the legality of their operation, that the legal instruments used are of significant importance for the assessment of the effectiveness of the performance of tasks related to combating infectious diseases, and thus ensuring health safety.
Keywords: pandemic, right to protection of health, infectious disease, health safety, public task